Evaluation of a serum-free culture medium for the enhanced vitrification cryosurvival of bovine in vitro-derived embryos - de Camargo, Janine; Rodrigues, Rafaela; Valente, Roniele Santana; Muller, Diego Borba; Vireque, Alessandra Aparecida; Belaz, Katia Roberta Anacleto; Bohrer, Rodrigo Camponogara; Basso, Andrea Cristina; Eberlin, Marcos Nogueira; Fontes, Patricia Kubo [UNESP]; Nogueira, Marcelo Fábio Gouveia [UNESP]; Sudano, Mateus José (Elsevier, 2022)
This is a feasibility study aimed to determine the effectiveness of a culture media designed to enhance embryonic cryopreservation based on laboratory-accessed quality phenotypes of in vitro produced bovine embryos. Recovered bovine oocytes were matured and fertilized in vitro and the presumptive zygotes that were obtained were randomly distributed into three culture media: (i) Control (C): modified synthetic oviduct fluid (mSOF) culture medium supplemented with 5 mg/mL BSA and 2.5% fetal calf serum; (ii) Medium A (MA): serum-free altered mSOF medium A; and iii) Medium B (MB): serum-free altered mSOF medium B. Embryos cultured in MA and MB presented a better viability after cryopreservation (P < 0.05) without affecting the production rates of blastocysts (P > 0.05, MB only) when compared to C. The MB-derived blastocysts had the highest (P < 0.05) hatching rate (26.1%, 53/203) and higher (P < 0.05) transferable embryos rate (92.1%, 187/203) compared to control-derived blastocysts (85.8%, 175/204). The total cell number in the embryos after vitrification/warming process was greater (P < 0.05) in the MA (144.9 ± 5.9) and MB (151.3 ± 7.1) compared to that in the control (121.4 ± 6.1). The number of large and giant cytoplasmic lipid droplets was reduced (P < 0.05) in MB-derived embryos compared to control-derived embryos. Additionally, the lipid profiles of MB-derived blastocysts were closely related to those observed in the in vivo-derived blastocysts. We observed different transcriptional profiles abundance of in vitro produced bovine embryos derived from control, MA and MB groups. Therefore, the novel MB culture medium increased embryonic cryosurvival and favored the production of bovine embryos in vitro with improved cellular and molecular laboratory-accessed quality phenotypes.
Keywords: Bovine embryo; Cryosurvival; Lipids; Vitrification